Effect of Age, Gender and Lip Length on Anterior Teeth Display - Rummana Aqeel, Muhammad Abubakar, Afsheen Zakir, Besam Babar, Kaswa Nayab, Ahmad Hassan Nadeem, Sajid Naeem (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the exposure of maxillary and mandibular teeth during lips at resting position and study the effect of age, gender and lip length on the anterior teeth display. Study design: Cross sectional observational study. Place and duration: Prosthodontic Department, Lahore Medical and Dental College from 5th June till 5th September 2022. Methodology: Selected subjects comfortably seated in dental chair. The resting position of upper lip length was recorded from subnasale to stomion at the facial midline. With participant at rest position; visible portion of anterior teeth were measured vertically from lower border of upper lip to incisal edge of incisors (canine tips at the mid-point) in maxillary teeth using vernier caliper. For mandibular teeth readings were taken from the lower lip upper border to the incisor’s edges of lower teeth (at the mid-point of canine cusp tip). Three readings of each tooth were recorded and mean value taken. Results: The visibility of anterior teeth was more prominently seen in females as compared to males but this finding was statistically insignificant. Decrease in the exposure of maxillary teeth and increase in the exposure of mandibular teeth was significantly found(p<0.05). More female participants were found with shorter lip lengthsas compared to males (p<0.05). Lip length association with increasing age was found to be significantly increased with increasing age. It was 8.99 ± SD 1.42 in age group less than 30 years, 9.02 ± SD1.57 in age group 31-50 and 10.01±SD 1.42 in participants above 50 years of age. Conclusion: There was no significant difference in exposure of anterior teeth at rest between gender. Females have shorter lip lengths than males. The upper lip length increases with increasing age. The exposure of maxillary anterior teeth significantly decreases and mandibular teeth increases with increasing age. Keywords: Anterior teeth, aging, gender, tooth display, tooth visibility, lip length.